55 Improving cost-effective prescribing of low-protein foods for dietary management for disorders of amino acid (AA) metabolism. (22nd November 2019) - Kidd, Catherine; Skeath, Rachel; Dixon, Marjorie
Abstract : Background: Disorders of AA metabolism require dietary protein restriction, l-amino acid supplementation and low-protein (LP) prescribed foods for metabolic control. The overall cost of LP diets to the NHS is estimated to be in the region of £12, 000 to £18, 000 per Phenylketonuria (PKU) patient per year, with costs varying according to patient age. Approximately 20% of this cost is attributed to food. Therefore, cost of LP foods for our PKU cohort (n=180) can be estimated to be in the region of £432, 000 to £648, 000 per year. Appropriate prescribing of LP foods is essential in a financially pressured NHS. Method: We collated a cost list of ACBS-endorsed LP foods (n=146) from 9 food manufacturers. Prices were obtained from the online BNF, or if unavailable from food manufacturer representatives. Foods were grouped into 19 categories according to type. Results: Prices were obtained for all foods, from the BNF (49%) or manufacturer representatives (51%). There was a wide range in costs both average costs within a category and between categories. Bread loaves were the cheapest (median £0.83/100g); savoury (burger/sausage/potato cake) mixes were the most expensive (median £5.31/100g). The biggest price range per 100g were crackers/crispbreads (£4.89) and biscuits (£4.11). Breakfast bars had the smallest price range per 100g (£0.34), but a high average cost. Comparing the cheapest and most expensive items in five basic ingredient categories (bread loaf, pasta, flour mix, biscuits, desserts) a prescription could range from £30.60 to £51.64. Discussion: A lack of transparency and wide variation in costs are two major barriers to cost effective prescribing. This situation requires dietitians to be knowledgeable about up to date food prices. Savings could be made if price information was easily available through the BNF for all LP foods. Balancing cost with patient choice is a challenge in clinical practice.